Effects of autosomal dwarf gene on growth and shank length of chicken (Bangladesh Veterinarian, 2013)
A partial diallel crossing of Rhode Island Red (RIR), White Leghorn (WLH), Fayoumi (FO), Desi normal (DN) and Desi dwarf (DD) produced RIR, WLH, FO, DN, DD, RIR x DD, WLH x DD and FO x DD offspring. A total 709 chicks, 75 RIR, 130 WLH, 100 FO, 70 DN, 66 DD, 80 RIR x DD, 80 WLH x DD and 108 FO x DD were reared for studying growth performance up to 18 weeks of age. At 19 weeks, the crossbreds RIR x DD, WLH x DD and FO x DD were separated into normal and dwarf genetic groups on the basis of shank length and thus 11 genetic groups, RIR, WLH, FO, DN, DD, RIR x DD normal, RIR x DD dwarf, WLH x DD normal, WLH x DD dwarf, FO x DD normal and FO x DD dwarf were obtained. Day-old weight differed significantly (P